Statistical QoS guarantees of a device‐to‐device link assisted by a full‐duplex relay. Issue 11 (9th August 2021) - Waqas Haider Shah, Syed; Li, Rongpeng; Mahboob Ur Rahman, Muhammad; Noor Mian, Adnan; Aman, Waqas; Crowcroft, Jon
Abstract: Device‐to‐device (D2D) communication is a promising technique to enhance the spectral efficiency for 5G and beyond cellular networks. Traditionally, D2D communication was considered solely as communication directly between two closely‐located devices, without any support from the available network infrastructure; however, this understanding limits the advantages of D2D communication. Relay‐assisted D2D communication was later proposed to allow devices to exchange data and extend coverage via relay strategy for transmission distance extension and capacity improvements. This work aims to determine the statistical quality‐of‐service (QoS) guarantees of a D2D link assisted by a full‐duplex relay by employing a commonly used analytical tool, the effective capacity (EC). We provide a closed‐form expression for the EC of relay‐assisted D2D communication, in which both the transmitter and the relay devices operate under individual QoS constraints. We also provide an analysis of the impact of mode selection on the EC of relay‐assisted D2D. Additionally, for the mode selection, we propose a novel multiple features‐based mechanism by utilizing all the features of a wireless link. We further provide a closed‐form solution for the non‐convex calibration problem of the optimal weights for these underlying features. Finally, simulation results demonstrate how the quality of self‐interference cancellation techniques impacts the EC of the relay‐assisted D2D. The results also show that the performance of our proposed mode selection mechanism with optimal weights outperforms the traditional mode selection mechanism. Abstract : This work aims to determine the statistical quality‐of‐service (QoS) guarantees of a D2D link assisted by a full‐duplex relay. We provide a closed form expression for the effective service capacity of the relay‐assisted D2D communication, in which both the transmit and the relay devices operate under individual QoS constraints.